SISTEM INFORMASI MANAJEMEN PEMESANAN PADA PERCETAKAN DOUBLE D MAKASSAR - Ryantomo; Sudirman; Marlina (STMIK KHARISMA Makassar, 2019)
This study aims to design and build a system that can be implemented on a computerized system to optimize the workings of the company Double